Writers' biographies and family histories in 20th- and 21st-century literature - Haffen, Aude; Guiheneuf, Lucie (Cambridge Scholars Publishing, 2018)
New creative forms of life writing have emerged over the past four decades. Following in the footsteps of the ""New Biographers, "" who more than half a century earlier had trusted art and imagination to uncover some truth about a singular existence, some late-twentieth and twenty-first century novelists, playwrights and essayists staged the lives of writers they loved, wanted to vindicate, or whose influence they needed to acknowledge and ward off. In other cases, they turned to another sort of genealogy and, blurring the lines between biography and autobiography, told the story of their paren